A Study of the Factors that Influence Learners’ Scientific Research Ability and the Strategies for Promoting It - Guixian Zhang, Mingfeng Fan (Forest Chemicals Review)
The cultivation of learners’ scientific research ability is an important element when it comes to training learners in higher educational institutes. In recent years, this research topic has received much attention in China. Focusing on current learners’ scientific research ability, this paper first analyses the important places for this topic and the trends in the research. Then, it outlines the factors that influence learners’ scientific research ability. By adopting interpretive paradigms, the paper constructs a multi-level hierarchical model of the factors influencing learners’ scientific research ability. It proposes the following measures and suggestions: strengthen the top-level design; enhance the mechanism for guarantees; integrate team resources; improve tutors’ level of scientific research and teaching; stimulate learners’ motivation to learn and enhance learners’ internal drive to develop their scientific research